Stable control of the fiber laser phased array under long-range turbulent atmosphere. (February 2022) - Huang, Guan; Lv, Guoyun; Fan, Yangyu; Geng, Chao; Li, Xinyang
Highlights: The basic principle and the challenges of fiber laser phased array are introduced. The negative impacts of noise and light propagation delay are analyzed. Gradient estimator based on lock-in amplifier is designed to solve problems. Comparison experiments are conducted in the free space with a distance of 40 m. Abstract: Fiber laser phased array (FLPA) plays an important role in the laser projection applications, such as free-space optical communication and directed energy. However, the turbulence suppression effect of FLPA is severely limited in the long-range atmospheric environment. In this paper, the basic principle of FLPA is introduced, and the practical challenges are analyzed in detail. To improve the performance of FLPA, a gradient estimator based on the lock-in amplifier (LIA-ES) is introduced. Experiments based on two-channel FLPA were conducted in the free space with the beam's propagation distance of 40 m, and the results showed that when the LIA-ES was employed, the energy transfer efficiency of FLPA was improved by 2.22%, and the stability was improved by 25.9%. In addition, when an equivalent beam's propagation distance of 30 km was introduced, the LIA-ES can improve the energy transfer efficiency by 62.7%, and improve the stability by 75.9%.